Efficiency and safety of fortification of food products with zinc required to control zinc deficiency disorders - Polumbryk, Maksim; Kravchenko, Victor; Kirkov, Marina (My University, 2012)
The authors of review present data on the physiological role, metabolism and biological availability of zinc in human body. Zinc is essential in pubertal development. It also has an antioxidant, anti-inflammatory, anticancer and possibly antidiabetic activity. A detailed analysis of zinc deficiency expansion in Ukraine and the World and main ways of its eliminating has been described. The most attention given of foods fortified with zinc.
Keywords: цинк; статеве дозрівання; фортифікація продуктів; антиоксидант; дефіцит нутрієнтів; zinc; fortification of products; antioxidant; nutrient deficiency; кафедра екології та екоменеджменту; кафедра харчової хімії